Pelatihan Teknologi Tepat Guna Pembuatan Abon Ikan Bandeng di Desa Totobo Kolaka - Yudi Agusman; Laode Asrun Azis; Achmad Lamo Said; Andi Iswan Muharram (Perhimpunan Ahli Teknologi Informasi dan Komunikasi Indonesia, 2024)
The technical training for milkfish floss production in Totobo Village, Kolaka, seeks to improve the competencies of coastal communities in transforming fishery products into value-added goods. This activity was executed across multiple sessions, encompassing the dissemination of materials on suitable technology, demonstrations of milkfish floss manufacture, collaborative practice, and engaging discussions. Assessment was conducted using observations, feedback surveys, and verbal contributions to gauge the efficacy of the training and participants' reactions. The research indicated that 87% of participants were satisfied with the training materials, 93% perceived the facilitator's delivery as clear, and 80% deemed the training relevant to their needs. Participants emphasized the need for subsequent training on product marketing tactics and packaging. This program effectively equipped the community with practical skills to foster local economic development. The program is advised for sustainable execution with modifications customized to the community's individual requirements.